Legal Consequences Regarding Buyers Who Do Not Complete the Land Sale and Purchase Deed Process (Case Study of Supreme Court Decision Number 120 K/Pdt/2016) - Putri, Azzahra Aulia Kresna; Winanti, Atik (Jurnal Daulat Hukum, 2024)
The "valid" requirement in making an agreement aims to have binding legal force and provide legal certainty for the parties. In accordance with Article 1457 of the Civil Code, a sale and purchase agreement is an agreement between a seller and a buyer. The seller is obliged to hand over the goods that are the object of the sale and purchase to the buyer, while the buyer is obliged to pay the price agreed upon by both parties. This agreement clearly regulates the rights and obligations of both parties. The purpose of this study is to determine the Legal Consequences Related to Buyers Who Do Not Complete the Land Sale and Purchase Deed Process (Case Study of Supreme Court Decision Number 120 K/Pdt/2016). The research method used is normative legal research. The conclusion of this study is that there are cases where buyers feel that they have transferred land rights in a sale and purchase transaction that is carried out only based on PPJB, as stated in the DecisionSupreme Court Number 120 K/Pdt/2016 in this case the buyer is not direct convert PPJB to AJB. This has been clearly regulated in Article 4 paragraph (1) of Government Regulation Number 24 of 1997 concerning Land Registration, which in essence explains: by registering land will provide legal certainty and legal protection to land rights holders. Furthermorein accordance with Article 19 paragraph 2 letter (c) of the Basic Agrarian Law, states that the certificate functions as a strong means of proof.